Hubungan Grit dan Persepsi Dukungan Supervisor dengan Komitmen Karier pada Karyawan Milenial - Crisanti, Hanna Tania Dwi; Rosatyani Puspita Adiati (Universitas Airlangga, 2024)
The shift in employee commitment today is towards their career rather than the organizations they work for. Career commitment is an individual’s attitude towards work which includes personal career goals. The aim of this study is to determine relationship grit and perceived supervisor support with employee’s career commitment. The 87 participants in this research were full-time employees of a company or organization, ages 24 to 35. This study uses 3 scales, namely Grit Scale developed by Duckworth, Perceived Supervisor Support Scale by Burns, and Career Commitment Scale by Carson and Bedeian. Data analysis support with program Jamovi 2.3.28. The findings of investigation suggest that there is a relationship between grit and perceived supervisor support with career commitment among millennial employees. Therefore, organizations need to consider approaches that focus on developing employee personal grit as well as strengthening the quality of the relationship between supervisor and employee to ensure employee long-term commitment to career and organizational success.